Does Social Cognitive Theory Explain Antenatal Care for Pregnant Women in Boyolali, Central Java? A Multilevel Analysis - Soraya, Mira Mashita; Prasetya, Hanung; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Healthy mothers play a central role in forming the foundation of future generations' health. The role of Antenatal Care (ANC) is quite crucial in the continuation of optimal pregnancy. The main purpose of pregnancy examination is to monitor fetal well-being and identify early risk factors during pregnancy. Although antenatal examination is considered important, some pregnant women have not made maximum use of pregnancy examination services due to various factors. This study aims to analyze the influence of the Social Cognitive Theory construct and the contextual influence of Posyandu on antenatal examination behavior. Subjects and Method: A cross-sectional study was conducted at 25 integrated health posts (Posyandu) in Boyolali Regency, Central Java from August to September 2024. A total of 200 pregnant women were selected using a simple random sampling method. The dependent variable was complete antenatal examination (≥ 6 visits). The independent variables were self-efficacy, outcome expectation, modeling, and reinforcement. Data collection was carried out using interviews, questionnaires, and ANC visit data from village midwives. Data were analyzed using multilevel multiple linear regression. Results: Multilevel analysis in this study showed that antenatal care visiting behavior in pregnant women increases along with high self-efficacy. (b=0.23; CI 95% = 0.09 to 0.36; p<0.001), positive outcome expectation (b=0.32; CI 95% = 0.21 to 0.43; p<0.001), reinforcement (b=0.38; CI 95% = 0.24 to 0.53; p<0.001), high education (b=0.28; CI 95% = -0.43 to 1.01; p=0.433), and high family income (b=0.27; CI 95%= -0.27 to 0.81; p=0.327). The effect of modeling, education and family income on antenatal visit behavior was not statistically significant. This multilevel analysis model also showed that the contextual effect in the integrated health post on antenatal visit behavior was quite large (ICC=24%). Conclusion: The frequency of complete antenatal check-ups will increase with high self-efficacy, positive outcome expectations, and reinforcement. Thus, social cognitive theory can be used to explain and predict routine antenatal check-ups. Variations in the posyandu level have a significant contextual effect on the behavior of complete antenatal check-ups (≥ 6 check-up visits).